Microwave assisted convenient synthesis of quino[2,3-b][1,5]benzoxazepines - Sonar, Swapnil S.; Sadaphal, Sandip A.; Pawar, Shivaji S.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
A convenient synthesis of quino[2,3-b][1,5]benzoxazepines from substituted 2-chloroquinoline-3-carbaldehyde and 2-hydroxyaniline by using stable, non-toxic and inexpensive catalyst 1,8-diazabicyclo-undecan-7-ene (DBU)/silica gel is described. This method affords the quino[2,3-b][1,5]benzoxazepines under the influence of microwave irradiation (360 W) in solvent-free conditions within short reaction times (2-3 min), giving high yields of products (93-96%). (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: 3-b][1; 5]benzoxazepines; DBU/silica gel; Microwave irradiatiom; Quino[2; Solvent-free